HUBUNGAN IMPLEMENTASI KEBIJAKAN LAHIR PROCOT PULANG BAWA AKTA DENGAN KUALITAS PELAYANAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANYUWANGI PROVINSI JAWA TIMUR - Ricky Ekasari Ramadhani Wicaksana (Jurnal LEX SPECIALIS, 2015)
Abstrak Be born birth got certificate Policy is Banyuwangi government policy which is Quick Wins Reforms and bureaucracy of Banyuwangi local governments in order to provide the ease, speed, accuracy , effective and efficient in the process of the birthonline certificate. This policy was formulated based on the problems facing The Population And Civil Registration Offices in Banyuwangi district is low awareness in the community to have a population administration documents mainly on the birth certificate. So the authors interested in taking research titled Relation of ImplementationBe born birth got certificate Policy To Official Service Population And Civil Registration Service Qualityin Banyuwangi district.In this study, using a mixed method research method research to the type of exploratory Sequential Model with two phases which qualitative and quantitative phase. With source data through interviews, literature review and questionnaire. The results of this research show the implementation of policies born be born brought home the deed is not as expected, because there are many encountered obstacles include lack of human resources employee / officer related services in information technology, a high rate of people who do not have birth certificates in 2015, and the high rate of birth certificates Offline management through sub-district or Department of Population And Civil Registration. And quality of service in The Department Of Population And Civil Registrationin Banyuwangi still low is still a lack of supporting facilities at partner hospitals or health centers, within the hospital were very much with the department of population and civil registration districts Banyuwangi that makes it difficult to coordinate, causing a delay in publishing deed. and based on the calculation of the correlation results a significant relationship between policy implementation and service quality policies brought home be born birth certificate.Keywords: Policy, service